Psychoemotional State of the Universities’ Teaching Staff in Uzbekistan - Salomova F.I.1, Akhmadalieva N.O.2, Sharipova S.A.3, Toshmatova G.O.3, Yarmukhamedova N.F.3, Mirsaga (Institute of Medico-legal Publications Pvt Ltd, 2020)
The results of assessing the psychophysiological state of modern teachers of Uzbekistan leading universitiesas the basis for the preventive measures development to maintain their health are presented. It is shown thatthe teachers’ cardiovascular system (CVS) functional state during the working day basically does not gobeyond physiological fluctuations, and the functional state of the central nervous system is characterizedby a decrease in the quality of the work performed. Revealed a high frequency of emotional burnout (EB)signs in teaching staff in comparison with the administrative and technical employees of universities;the average statistical indicators of the signs of the teaching staff of different universities do not havestatistically significant differences. The average level frequency of emotional exhaustion among the teachingstaff members is 52-60%, a high level of personal achievement reduction - 44-50%; the average level ofdepersonalization is 22-40%. For the EB signs frequency, the work experience at the university matters; atthe beginning of the academic year, emotional burnout indicators are less pronounced than at the end.